Pembelajaran Process Oriented Guided Inquiry Learning (POGIL) diintegrasikan Discovery Learning untuk meningkatkan kemampuan berpikir analisis peserta didik: (Process Oriented Guided Inquiry Learning (POGIL) integrated with Discovery Learning to improve students' analytical thinking skills) - Calvin Talakua; Marlen Sahureka (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2021)
This research was conducted based on the results of initial observations through interviews with Biology subject teachers for class X at Trana Christian High School, it was found that the implementation of the 2013 curriculum in schools had not been going well, because teachers often used lecture methods, and discussions in the learning process . This affects the analytical thinking ability of students. The purpose of this study was to determine the analytical thinking ability of students of class X MIA Christian High School Trana through Process Oriented Guided Inquiry Learning (POGIL) and Discovery Learning on the Classification of Living Things. This type of research is descriptive qualitative research, with the research subjects are all students of class X MIA Christian High School Trana, totaling 23 people. Data collection techniques used in this study were observation sheets, tests, questionnaires, and documentation.The results showed that the analytical thinking skills of 23 students of class X MIA Christian High School Trana through the integration of POGIL learning and Discovery Learning obtained an average total score presentation of 80% of students in the good category, and 20% in the fairly good category. Abstrak. Penelitian ini dilakukan berdasarkan hasil observasi awal melalui wawancara dengan guru mata pelajaran Biologi kelas X di SMA Kristen Trana diketahui bahwa, penerapan kurikulum 2013 di sekolah belum berjalan dengan baik, dikarenakan guru sering menggunakan metode ceramah, dan diskusi dalam proses pembelajaran. Hal ini berpengaruh pada kemampuan berpikir analisis peserta didik. Tujuan penelitian ini adalah untuk mengetahui kemampuan berpikir analisis peserta didik kelas X MIA SMA Kristen Trana melalui pembelajaran Process Oriented Guided Inquiry Learning (POGIL) dan Discovery Learning pada materi Klasifikasi Makhluk Hidup. Jenis penelitian ini adalah penelitian deskriptif kualititatif, dengan subjek penelitian adalah seluruh peserta didik kelas X MIA SMA Kristen Trana yang berjumlah 23 orang. Teknik pengumpulan data yang digunakan dalam penelitian ini adalah lembar observasi, tes, penyebaran angket, dan dokumentasi. Hasil Penelitian menunjukan bahwa kemampuan berpikir analisis dari 23 peserta didik kelas X MIA SMA Kristen Trana melalui integrasi pembelajaran POGIL dan Discovery Learning memperoleh rata-rata presentasi skor total peserta didik 80% dengan kategori baik, dan 20% berada pada kategori cukup baik.